Effects of free organic groups in carbon nanotubes on glass transition temperature of epoxy matrix composites. (30th October 2015) - Jiang, Cai; Zhang, Jianwei; Lin, Shaofeng; Ju, Su; Jiang, Dazhi
Abstract: Molecular dynamics (MD) simulation and differential scanning calorimetric (DSC) test for epoxy resin composites embedded with carbon nanotubes (CNTs) were conducted to study effects of free organic groups in the CNTs on glass transition temperature ( T g ) of the composites. Three types of CNTs including pristine, with hydroxyl (–OH) groups and carboxyl (–COOH) groups, respectively, were involved in the investigation. Both simulation and experimental results showed that T g s of the CNT/epoxy composites are higher than that of the neat epoxy, T g s of the composites randomly embedded with functionalized CNTs were lower than that with pristine CNTs, and T g of the composites embedded with COOH-CNTs was much lower than that with OH-CNTs. This was attributed to the weaker interactions between the embedded functionalized CNTs and the polymer matrix, due to the further distances and larger inter-space around the CNTs caused by free –OH or –COOH groups in the CNTs. Highlights: There is still lack of an agreement on whether addition of CNTs caused an increase or decrease in glass transition temperature ( T g ) of CNT/polymer composites in previous studies, the change of T g of the CNT/polymer composite could be related to contents, aspect ratio, functionalization of the CNTs and so on. Effects of free organic groups in CNTs on T g s of the CNT/epoxy composites were investigated by both of the molecular dynamic model and the DSC measurement in the submitted paper. Results showed that T g s of the CNT/epoxy composites are higher than that of the neat epoxy, and T g s of the composites randomly embedded with functionalized CNTs were lower than that with pristine CNTs, and T g of the composites embedded with COOH-CNTs was much lower than that with OH-CNTs. Related the T g variation of the CNT/epoxy composites with the organic groups in the CNTs.